A case study on choosing effective nature based solutions for climate change adaptation in Istanbul - ORAK, NUR HANİFE (My University, 2023)
Climate change effects are increasing in intensity and frequency year by year, affecting biodiversity, human beings, and cities directly and adversely. Selecting the most suitable nature-based solution (NbS) in order to combat the effects of climate change, according to the specific needs of each district, is an important subject that needs to be investigated extensively. In this study, a mathematical model is developed to determine the most effective NbS or the configuration of different NbS in the city of Istanbul in Türkiye. Geographic information system program and Google Earth alongside the data obtained from publicly available national sources are used in the classification of districts, which helps defining land use types using the Local Climate Zone method. The Bayesian Network model is used to select the optimum NbS according to certain characteristics for structuring knowledge or beliefs relating to a domain, or for supporting decision making. The developed methodological framework will help selecting the most effective NbS according to specific area characteristics or configurations in different land use scenarios that can be applied in any region or city, which in return will provide practical, fast, and economic information in the long term for the decision makers and stakeholders.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Engineering, Computing & Technology (ENG)